Quantitative determination of superoxide in plant leaves using a modified NBT staining method - Grellet Bournonville, Carlos Froilan (2011)
Introduction - In plants, the ROS (reactive oxygen species) level is tightly regulated because their accumulation produces irreversible damage leading to cell death. However, ROS accumulation plays a key role in plant signaling under biotic or abiotic stress. Although various methods were reported to evaluate ROS accumulation, they are restricted to model plants or provide only qualitative information. Objective - Develop a simple method to quantify superoxide radicals produced in plant tissues, based on the selective extraction of the formazan produced after nitroblue tetrazolium (NBT) reduction in histochemical staining. Methodology - Plant leaves were stained with a standard NBT method and the formazan precipitated in tissues was selectively extracted using chloroform. The organic phase was dried and formazan residue dissolved in dimethylsulfoxide-potassium hydroxide and quantified by spectrophotometry. The method was tested in strawberry plant leaves under different stressing conditions. Results - Formazan extracted from leaves subjected to stress conditions showed similar absorption spectra to those obtained from standard solutions using pure formazan. Calibration curves showed a linear relationship between absorbance and formazan amounts, within the range 0.5-8 μg. Outcomes suggested that formazan was retained in the solid residue of leaf tissues. This protocol allowed us to quantify superoxide radicals produced under different stress conditions. Conclusions - Chloroform allowed a selective formazan extraction and removal of potential endogenous, exogenous or procedural artefacts that may interfere with the quantitative determination. This protocol can be used to quantify the superoxide produced in plant tissues using any traditional qualitative NBT histochemical staining method.